A high‐power, high‐repetition‐rate THz source for pump–probe experiments at Linac Coherent Light Source II. (15th June 2020) - Zhang, Z.; Fisher, A. S.; Hoffmann, M. C.; Jacobson, B.; Kirchmann, P. S.; Lee, W.-S.; Lindenberg, A.; Marinelli, A.; Nanni, E.; Schoenlein, R.; Qian, M.; Sasaki, S.; et al.
Abstract : A two‐bunch scheme to generate high‐power, high‐repetition‐rate THz radiation for pump–probe experiments at LCLS II is studied. The two‐bunch beam dynamics, the THz wiggler and radiation are described, as well as the transport system bringing the THz pulses from the wiggler to the X‐ray experimental hall. Abstract : Experiments using a THz pump and an X‐ray probe at an X‐ray free‐electron laser (XFEL) facility like the Linac Coherent Light Source II (LCLS II) require frequency‐tunable (3 to 20 THz), narrow bandwidth (∼10%), carrier‐envelope‐phase‐stable THz pulses that produce high fields (>1 MV cm −1 ) at the repetition rate of the X‐rays and are well synchronized with them. In this paper, a two‐bunch scheme to generate THz radiation at LCLS II is studied: the first bunch produces THz radiation in an electromagnet wiggler immediately following the LCLS II undulator that produces X‐rays from the second bunch. The initial time delay between the two bunches is optimized to compensate for the path difference in THz transport. The two‐bunch beam dynamics, the THz wiggler and radiation are described, as well as the transport system bringing the THz pulses from the wiggler to the experimental hall.